Mediações entre políticas de lazer e experiências culturais: um estudo de caso a partir do olhar da gestão do PELC-Bahia - Jenifer Lourenço Borges Vieira (2022)
The present study focuses on the cultural experiences conceived within the scope of the Sport and Leisure Program of the City (PELC), developed in the State of Bahia by the Superintendence of Sports of the State of Bahia (SUDESB) in partnership with the Ministry of Sport (ME) / Federal University of Minas Gerais (UFMG) between 2017 and 2019, the effective period of the program. Understanding leisure from the diversity of cultural experiences lived/developed in PELC-Bahia can enable an analysis of how the right to leisure, promoted by the program, helps (or not) in the elaboration of identity formation processes regarding cultural identity of the people, from the perspective of the management team. Thus, the problem of this study turns to the understanding of the cultural mediation processes that took place within the scope of the program and that, through the cultural experiences developed in the PELC, enabled or not the formation and/or appreciation of the cultural identity of those involved from the perspective of leisure studies. Based on the understanding of leisure as a dimension of culture that dialogically completes itself with the notion of the leisure experience as a social practice, considering data from PELC-Bahia that demonstrate the movement of such cultural experiences in the program. The study presents, as an empirical basis for the analysis, semi-structured interviews carried out with the general coordination, pedagogical coordination, nucleus coordinators and social agents, in addition to a questionnaire applied to nucleus coordinators and social agents who worked in the program.